Building the dynamic diffusion layer for SPN block ciphers based on direct exponent and scalar multiplication - Luong, Tran Thi (Journal of Science and Technology on Information security, 2022)
Abstract— Maximum Distance Separable (MDS) matrices have been applied not only in coding theory but also in the design of block ciphers and hash functions. In this paper, we propose algorithms for building a dynamic diffusion layer for SPN block ciphers based on the direct exponent and scalar multiplication. The proposed dynamic algorithms contribute to improving the security of SPN block ciphers against strong attacks on block ciphers such as linear attacks, differential attacks.